Managing the military patient with syncope. Issue 3 (5th August 2015) - Parsons, Iain T; Cox, A T; Mollan, I A; Boos, C J
Abstract : Syncope is a relatively common occurrence in military populations. It is defined as a transient loss of consciousness due to global cerebral hypoperfusion, characterised by a rapid onset, short duration and a spontaneous and complete recovery. While the symptom of syncope is easily elicited, discovering the mechanism can be more problematic and may require a plethora of diagnostic tests. The aim of this paper is to review current evidence pertaining to the classification, investigation and management of syncope, from a military perspective. Emphasis is placed on assisting primary healthcare professionals in the assessment and management of syncope, in the UK and on operations, while providing explicit guidance on risk. The occupational limitations required in safely managing patients with syncope are stressed along with the potential long-term limitations.